La manifestation de l’émotion dans un débat d’idée - Hassiba Chaibi (OpenEdition, 2020)
This article reports on the treatment of the issue of affective rhetoric in a mediated debate of ideas. The objective is to show, the affected utterance of the writer Fatou DIOME, that is to say how it proceeds to semiotize the emotions through the structuring of discursive forms at the service of the interpretation of a situation problematic which is in the case of the corpus retained for the analysis "illegal immigration".